Muslim women and religious authorities in the mass media in Malaysia - Ismail, Norbani (2010)
The issues of participation and contribution of Muslim women in public spheres have been widely discussed in the academic circles. Up to the present day, many Muslim women in patriarchal Islamic societies are still struggling to have a role in public life. On the other hand, in some parts of the Muslim world women enjoy a much better status. They are welcome to contribute to and actively engage in their communities. This study will focus on Muslim women-preachers in contemporary Malaysia. The emphasis is on their ideas and preaching as expressed in the mass media outlets. The three preachers chosen for this study are: Dr. Sharifah Hayati Syed Ismail, a professor of Islamic studies at the National University of Malaysia, Siti Nor Bahyah Mahamood, a preacher and a motivator who owns a motivational company, and Dr. Fatma al-Zahra, an Egyptian medical doctor who migrated to Malaysia. These preachers have expressed religious responses and opinions to the masses through different media channels such as the national television, printed newspapers, as well as magazines. Oftentimes, they are also invited to give occasional lectures at the local and international mosques. The paper seeks to answer the following questions: What are the issues that feature prominently in the lectures delivered by Muslim women preachers?; Are their works and the issues they talk about only limited to the ‘women’ issues?; What are the challenges that these female preachers face in doing their job?; Do they feel being discriminated against?; What motivates them to engage in such work?; Are their views and opinions accepted and valued by the general public?; Are their views accepted because of their religious education?; Are their targeted groups mostly women? This study will analyze their works as expressed in the television programs, newspaper columns and magazines, and lectures at the mosques. The researcher will also conduct personal interviews with the female preachers.